Hubungan Tingkat Aktivitas Fisik, Kualitas Tidur Dan Pengetahuan Gizi Seimbang Terhadap Status Gizi Lebih Mahasiswa Fikes Universitas Indonesia Maju Tahun 2023 - Lulu’ul Badriyah; Arisman Gea; Ema Hulina W. Sitepu (Program Studi Gizi UNSIKA, 2024)
Nutritional status is the output of food consumed by a person. Good nutritional status is influenced by a balanced nutritional intake. The balance between energy intake and expenditure from the body is influenced by physical activity. This study aims to determine the relationship between physical activity levels, sleep quality and knowledge of balanced nutrition on the nutritional status of advanced Indonesian university health students in 2023. This research uses a cross-sectional method. The research was conducted in July 2023, the sample in this study consisted of 95 students. Sampling used probability sampling techniques. The bivariate analysis used was the chi-square test. The results of the univariate test on the nutritional status variable showed that the majority of respondents had normal nutritional status, respondents who had high activity, respondents who had poor sleep quality and respondents who had moderate knowledge of balanced nutrition. The results of the bivariate analysis showed that there was no relationship between physical activity and nutritional status, there was no relationship between sleep quality and nutritional status and there was no relationship between knowledge of balanced nutrition and nutritional status. It can be concluded that this research has not succeeded in proving the existence of a relationship between three independent variables including physical activity, sleep quality and knowledge of balanced nutrition on nutritional status as the dependent variable. Keywords: physical activity, sleep quality, knowledge of balanced nutrition, nutritional status.